Relations between the Czech Legion’s Representatives and the Opposing Political Forces in the Volga Region: from Negotiations to War - Berik K. Dulatov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2018)
The article deals with the issues of mutual relations of Czechoslovak legionaries with local executive authorities in the territory of the Volga region and the Southern Urals. Initially, Czechs, as citizens of Austria-Hungary, were involved in the war against the Russian Empire according to military duty. At a subconscious level, Czechs and Slovaks felt ethnic solidarity and closeness with the Slavic peoples. At the beginning of the Civil War, according to the established Soviet tradition, they were involved in the Czech (Czechoslovak) legion, which conducted military and ideological war against the Soviet regime. In this perspective, there is a need to study the reasons for the participation of Czechs in the so-called Revolt of the Czechoslovak Legion, to reveal the factors that led to the beginning of the Czech rebellion and to name the initiators of this event. Of considerable interest are the problems of studying political attitudes and sympathies of Czech prisoners of war to events on the territory of the empire on the eve of the outbreak of the revolution and in the course of the Civil War. The problem of the participation of Czechs and Slovaks in the Red Army, and in other military formations that are ideologically close to the Soviet regime, are also understudied in historiography.